The Context, Input, Process, and Product Evaluation Model on English Language Teaching at Public Health Study Program - Sukarni, Sri (IJECA (International Journal of Education and Curriculum Application), 2022)
Evaluation of English teaching is carried out to determine the achievement of program objectives and provide recommendations for program improvement. This study aims to evaluate the implementation of English Language Teaching to identify its effectiveness in achieving the objectives of the Public Health Study Program curriculum. In this study, the CIPP (Context, Input, Process, and Product) evaluation model was applied. This research was conducted at the Public Health Study Program, Faculty of Sport and Public Health, Mandalika University of Education. The population in this study was the first semester students of Public Health study program in the amount of 133 students. In determining the number of samples, there were 46 students chosen as samples by using simple random sampling technique, and 1 English lecturer and the Head of Public Health study program as the participants in this study. This study was an evaluative study utilizing a mixed-method research design. The data gained from the questionnaire were analysed by using descriptive quantitative whereas, the data obtained from interview and class observation were analysed qualitatively. Based on the findings of the study, it was found that for context dimension got a Percentage of Effectiveness of 78.52; input dimension got a Percentage of Effectiveness of 59.47; process dimension got a Percentage of Effectiveness of 76.74, and product dimension got a Percentage of Effectiveness of 51.86.  Based on the result of the study, it was concluded that the implementation of teaching English in Public Health study program has not been effective. It is recommended that language skills and language components are integrated since those elements can support communication ability stated in the curriculum of Public Health study program.